Penerapan Search Engine Optimization untuk Website Dinamis Pada UKM Furniture Boyolali - Indra Ava Dianta; ahmad ashifuddin aqham (Jurnal Pengabdian Pada Masyarakat Indonesia, 2022)
The purpose of this community service is to provide counseling and training on website creation as a good online digital marketing tool, understand website creation, can apply the knowledge gained and be involved in managing online marketing.